Thermographical monitoring of structure transformations in Cd₁-ₓZnₓTe milts - Feychuk, P.I.; Shcherbak, L.P.; Kopach, O.V. (Functional Materials, 2005)
Thermal effects in the Cd₁-ₓZnₓТе (х = 0; 0.04; 0.1) melts at lowering under temperature gradient at a speed of 1 to 10 mm/h and at isothermal holding at certain temperatures have been monitored using the derivative thermal analysis method. The multistage character of the nucleation and the crystallization centers formation in the investigated melts has been discuss. That conclusion has been drawn basing on the presence of discrete temperature intervals where temperature oscillations occur in the cooling melt in the certain thermodynamics conditions. Методом производного термического анализа проведен мониторинг тепловых эффектов в расплавах Cd₁-ₓZnₓТе (х = 0; 0.04; 0.1) при опускании в градиенте температур со скоростью 1-10 мм/ч и во время изотермической выдержки при определенных температурах. Обсуждается многостадийный характер формирования зародышей и центров кристаллизации в исследованных расплавах. Вывод о последнем основан на существовании дискретных интервалов температур, в которых при определенных термодинамических условиях охлаждения расплава происходят осцилляции температуры. Методом похiдного термiчного аналiзу проведено монiторинг теплових ефектiв у
розплавах Cd₁-ₓZnₓТе (х = 0; 0,04; 0,1) при опусканнi у градiєнтi температур та пiд час iзотермiчної витримки при певних температурах. Обговорюється багатостадiйний характер формувания зародкiв та центрiв кристалiзацiї у дослiджених розплавах. Такий висновок зроблено на пiдставi iснування дискретних iнтервалiв температур, в яких при певних термодинамiчних умовах охолодження розплаву вiдбуваються осциляцiї температури.